1987
DOI: 10.1021/ic00253a020
|View full text |Cite
|
Sign up to set email alerts
|

Anion-induced quenching of excited bis(2,9-dimethyl-1,10-phenanthroline)copper(1+)

Abstract: As the counterion is varied, the emission quantum yield of *Cu(dmp)2+ (dmp is 2,9-dimethyl-1,10-phenanthroline) varies by as much as 30% in fluid CH2C12 while the lifetime is unchanged. These results are explained in terms of a static quenching mechanism that occurs within ion pairs present in solution. Anions do not quench the emission of the corresponding complex of 2,9-diphenyl-1,10-phenanthroline, and BPh4" does not quench the emission of *Cu(dmp)2+, even though significant ion pairing occurs. On the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
2

Year Published

1987
1987
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 4 publications
(4 reference statements)
0
7
0
2
Order By: Relevance
“…Recent reports have indicated that, in addition to the effect from the steric properties of the diimine ligand, the lifetime of the MLCT excited state is influenced by the extent of p-delocalization in the diimine ligand [8]. Exploitation of these effects has served as the basis for synthetic tuning of excited-state properties, an area that has become an important focus of recent research efforts on approaches to solar-energy conversion [4] [18].…”
mentioning
confidence: 99%
“…Recent reports have indicated that, in addition to the effect from the steric properties of the diimine ligand, the lifetime of the MLCT excited state is influenced by the extent of p-delocalization in the diimine ligand [8]. Exploitation of these effects has served as the basis for synthetic tuning of excited-state properties, an area that has become an important focus of recent research efforts on approaches to solar-energy conversion [4] [18].…”
mentioning
confidence: 99%
“…The MLCT transitions can be tuned to lower energies by introducing a ligand with a low-lying p* molecular orbital. The steric, electronic, and conformational interactions influence the redox potential of these complexes and modify their excited-states properties [15]. A thorough understanding of these effects will serve as the basis for a rational design of complexes with specific and predictable properties [3] [19].…”
mentioning
confidence: 99%
“…Στο παραπάνω σχήμα δεν περιλαμβάνεται ένα τέτοιο ενεργειακό όρος ωστόσο διάφορες διαδικασίες όπως κάποιο στάδιο απογύμνωσης από το διαλύτη ή δομικής αναδιοργάνωσης του συμπλόκου θα μπορούσε να επάγει κάποια ενεργειακή απαίτηση για την ενεργοποίηση του φαινομένου. [82,86,87]. Σχήμα 13.…”
Section: α32 φασματοσκοπία απορρόφησηςunclassified
“…McMillin και Goodwin κατέληξαν το 1987 [87] ότι μία ποικιλία από συναρμοστικά ανιόντα μπορούν να αποσβέσουν τη διεγερμένη MLCT κατάσταση των συστημάτων του τύπου [Cu(NN) 2 ] + μέσω ενός μηχανισμού σύναψης (associative mechanism) και ότι σε αραιά διαλύματα η επάρκεια της απόσβεσης εξαρτάται από την ισορροπία σχηματισμού ζευγών ιόντων. Κατά συνέπεια οι κβαντικές αποδόσεις σε διάλυμα εξαρτώνται από τη φύση τόσο του ανιόντος όσο και του διαλύτη.…”
Section: ειδικότερα όσον αφορά την επίδραση των αντισταθμιστικών ανιόντων οιunclassified
See 1 more Smart Citation